ANALISIS PENGARUH INTELLECTUAL CAPITAL, PENGUNGKAPAN SUSTAINABILITY REPORT, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Narcisus Jumadi; Julianti Sjarief (SIMAK, 2021)
The purpose of this research to analyze the effect of intellectual capital, sustainability report disclosure, and firm size on the financial performance of non-financial companies listed on the Indonesia Stock Exchange for the 2017-2020. In this study, there were 66 samples from 18 companies. The data collection method used is purposive sampling method. The data analysis method used is multiple linear regression analysis. The results showed that intellectual capital has a significant positive effect on financial performance, sustainability reports disclosure has a significant negative effect on financial performance, and firm size has no significant effect on financial performance.